The man in the iron mask - Dumas, Alexandre 1802-1870.; Wallace, Randall; DiCaprio, Leonardo; Irons, Jeremy; Malkovich, John.; Depardieu, Gerard; Byrne, Gabriel; Parillaud, Anne.; United Artists Corporation; MGM Home Entertainment Inc.; Metro-Goldwyn-Mayer.; Twentieth Centery Fox Home Entertainment ([Los Angeles, Calif.] MGM Home Entertainment, 1999)
Paris is starving, but the King of France is more interested in money and bedding women. When a young soldier dies for the sake of a shag, Aramis, Athos and Porthos band together with a plan to replace the king. Unknown to many, there is a 2nd king, a twin, hidden at birth, then imprisoned for 6 years behind an iron mask. All that remains now is D'Artagnan, will he stand against his long time friends, or do what is best for his country?
Summary taken from website: http://www.imdb.com/title/tt0120744/plotsummary
Title from container.
Based on the novel by Alexandre Dumas.
Originally released as motion picture in 1998.
Editor, William Hoy.
Leonardo Dicaprio, Jeremy Irons, John Malkovich, Gerard Depardieu, Gabriel Byrne, Anne Parillaud.
Rated PG-13.
Keywords: Twins -- Drama; Feature films; Action and adventure films; France -- History -- Louis XIV, 1643-1715 -- Drama